Jesus for Zanzibar : narratives of Pentecostal (non-)belonging, Islam, and nation - Olsson, Hans (Researcher), (Studies of Religion in Africa;, 2019)
In Jesus for Zanzibar: Narratives of Pentecostal (Non-)Belonging, Islam, and Nation Hans Olsson offers an ethnographic account of the lived experience and socio-political significance of newly arriving Pentecostal Christians in the Muslim majority setting of Zanzibar. This work analyzes how a disputed political partnership between Zanzibar and Mainland Tanzania intersects with the construction of religious identities. Undertaken at a time of political tensions, the case study of Zanzibar's largest Pentecostal church, the City Christian Center, outlines religious belonging as relationally filtered in-between experiences of social insecurity, altered minority / majority positions, and spiritual powers. Hans Olsson shows that Pentecostal Christianity, as a signifier of (un)wanted social change, exemplifies contested processes of becoming in Zanzibar that capitalizes on, and creates meaning out of, religious difference and ambient political tensions.